Behavioral and Neuropathological Changes After Toxoplasma gondii Ocular Conjunctival Infection in BALB/c Mice - Soares, Gabrielly Lisboa da Silva; Leão, Ellen Rose Leandro Ponce de; Freitas, Sinara Franco; Alves, Raissa Maria Carvalho; Tavares, Naiana de Paula; Costa, Maria Vitória Nascimento; Menezes, Gabriel Castro de; Oliveira, Jhonnathan Henrique Palheta de; Guerreiro, Luma Cristina Ferreira; Assis, Alexa Camila Lopes de; Araújo, Sanderson Corrêa; Franco, Felipe Tuji de Castro; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
It is known that ocular infection with Toxoplasma gondii causes toxoplasmosis in mice. However, following ocular infection with tachyzoites, the cause of the accompanying progressive changes in hippocampal-dependent tasks, and their relationship to the morphology and number of microglia is less well understood. Here, in six-month old, female BALB/c mice 5μl of a suspension containing 48.5x106 tachyzoites/mL were introduced into the conjunctival sac; control groups received an equal volume of saline. Before and after instillation, all mice were subject to an olfactory discrimination (OD) test using predator (cat) feces and to an open field (OF) task. After the behavioural tests, the animals were culled at either 22- or 44-days post-instillation (dpi), and the brains and retinas were dissected and processed for immunohistochemistry. The total number of Iba 1 immunolabeled microglia in the molecular layer of the dentate gyrus were estimated and three-dimensional reconstructions of the cells were evaluated. Immobility was increased in the infected group at 12, 22 and 43 dpi, but greatest immobility was observed at 22 dpi and was associated with reduced line crossing in the OF and distance travelled. In the OD test, infected animals spent increasingly more time in the compartment with feline faecal material from 14dpi until 43dpi. No OD changes were observed in control group. The number of microglia was increased at 22dpi, but returned to control levels by 44dpi. These changes were associated with the differentiation of T. gondii tachyzoites into bradyzoite enclosed cysts within the brain and retina. Thus, infection of mice with T. gondii alters exploratory behavior, gives rise to a loss in predator’s odour avoidance from 2 weeks after infection, and increased microglia number and altered their morphology in the molecular layer of the dentate gyrus.